2019
DOI: 10.1080/10942912.2019.1671453
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals in some date palm fruit cultivars in Saudi Arabia and their health risk assessment

Abstract: Date fruits have ample amount of beneficial minerals but owing to diverse causes may contract with heavy metals and contaminants during field, processing, or transportation posing health challenges to consumers. Hence, current research explored the toxic heavy metals (Al, As, Cr, Pb, Cd, and Sb) levels in seven date varieties (Sakay Mabroum, Sakay Normal, Rashadya Al-qaseem, Barny Al-Madina, Eklas Al-Hassa, Safawy Al-Madina, Kadary) collected from different locations of Saudi Arabia by applying inductively cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…The results indicated that, the order of EDI of all the investigated metals were Fe > Cu > Zn > Ni > Cd > Cr > Cu. EDIs values of these metals were lower than their corresponding maximum tolerable daily intake of Cd, Cr, Cu, Fe, Ni and Zn with values of 0.07, 0.2, 3.0, 0.8, 0.3, and 1, respectively (Woldetsadik et al, 2017;Alipour and Banagar 2018;Deng et al, 2019), which indicates that consuming ginger has negligible health risk (Salama et al, 2019).…”
Section: Risk Assessmentmentioning
confidence: 89%
“…The results indicated that, the order of EDI of all the investigated metals were Fe > Cu > Zn > Ni > Cd > Cr > Cu. EDIs values of these metals were lower than their corresponding maximum tolerable daily intake of Cd, Cr, Cu, Fe, Ni and Zn with values of 0.07, 0.2, 3.0, 0.8, 0.3, and 1, respectively (Woldetsadik et al, 2017;Alipour and Banagar 2018;Deng et al, 2019), which indicates that consuming ginger has negligible health risk (Salama et al, 2019).…”
Section: Risk Assessmentmentioning
confidence: 89%
“…While dates have positive biological effects, concerns have been raised about their potential concentrations of heavy metals [ 126 , 127 ]. Exposure to heavy metals can result in cardiovascular diseases, encephalopathy, renal dysfunction, dementia, and certain cancers [ 128 , 129 ].…”
Section: Future Considerationsmentioning
confidence: 99%
“…Exposure to heavy metals can result in cardiovascular diseases, encephalopathy, renal dysfunction, dementia, and certain cancers [ 128 , 129 ]. A recent study of seven date varieties collected from different locations in Saudi Arabia noted that aluminum, chromium, and antimony were within a safe range based on the maximum allowable levels set by the World Health Organization, while arsenic, lead, and cadmium exceeded the upper limit in some of the date cultivars [ 126 ]. Numerous environmental factors can increase concentrations of heavy metals such as mining, fertilizer applications and industrial emissions, as well as naturally occurring amounts normally found in some soils [ 129 ].…”
Section: Future Considerationsmentioning
confidence: 99%
“…The change in the level of cadmium that occurs between samples collected from the three studied sites may be due to the ability of plant absorption that depends on the content of heavy minerals in the soil and genetic makeup of the plant. Cadmium can result in diseases of kidney, lungs and also can lead to skeleton problems as it is related with cancerous risk as compared to lead which is non-cancer risk factor (Salama et al, 2019). Current study elucidated low level of Cd as compared to Pb revealing uptake of heavy metals owing to plant ability to accumulate them (Ahmed and Al-Swaidan.…”
Section: Discussionmentioning
confidence: 86%
“…Lead concentration may be attributed to various causes where automobile contribute to a greater extent followed by the use of lead-based pesticides in crop protection. The deposit of lead on edible tissues of crops also depends upon air pollution, air dust, distance from the roads side as well as traffic loads (Salama et al, 2019). Hussain et al analyzed dates imported into Kuwait and found that dates collected from different location were differing in Pb contents and some of the samples were exceeding the MAL values.…”
Section: Discussionmentioning
confidence: 99%